THE EFFECTIVENESS OF SURVEILLANCE TRAINING ON IMPROVING KADER SKILLS - Abu Kasim; Arfah Husna (RADJA PUBLIKA, 2022)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Aceh is the third highest prevalence of stunting in children under five in Indonesia, which is 37.3%. Compared to the national average, only 30.8%. The prevalence of stunting in Aceh is much higher than the provinces of Papua, Maluku and other regional provinces in Indonesia. The purpose of this study was to determine the understanding of cadres in carrying out the tasks carried out as Integrated Health Center cadres in dealing with stunting problems in Kaway XVI sub-district. The research method is a quasi-experimental method. The data were collected using a cross-sectional design method, with pretest and posttest questionnaires on a total population of 18 Integrated Health Center cadres and 18 samples of Integrated Health Center cadres observations, with purposive technique and then tested using the dependent t test. The understanding of Integrated Health Center cadres increased from the initial understanding of the average value from 58.61 to 67.50. And the obtained p value of 0.004 means that there is a relationship between providing education and increasing knowledge of Integrated Health Center cadres. The conclusion of the intervention is that it is able to increase the knowledge of Integrated Health Center cadres especially West Aceh, especially Kaway XVI. Suggestions for Integrated Health Center cadres that are necessary to do a full-down so that understanding is increased in dealing with stunting rates in Kaway XVI.